DIRECT YIELD FORMULAS FOR SERIAL BONDS. - Snyder, Ralph W. (The Accounting Review, 1955)
The yield formulas for irregular installment payments can be used to find the yield or effective rate of interest on an issue of serial bonds. Unequal retirement installments or intervals of payment, deferred first coupons, even maturity premium requirements, with any or all of these the general installment payment formulas will produce a reasonable approximation, usually very close and sufficient for an amortization schedule, to the yield rate. If, however, the serial issue is such that every bond by itself is a simple and complete bond, that is, with no initial coupon irregularities and no premium due on maturity, it is possible to derive a yield formula but which can be used by considering only the maturity payments and ignoring the coupon payments. This will be so regardless of inequalities in amounts and intervals of the serial maturities themselves. The article presents such a formula. The shortening of the summation process can be carried to its limit, and is most easily demonstrated, with a perfectly regular issue, but even with an issue having irregularities, short cuts are still available.